SISTEMATIK LITERATUR REVIEW: STRATEGI IHRM UNTUK MENINGKATKAN RETENSI EKSPATRIAT - Ghozali, Abbiyu M. (Jurnal Bina Bangsa Ekonomika, 2025)
Expatriate retention is a major challenge faced by global organizations in the era of globalization. High rates of expatriate assignment failures can lead to financial, operational, and reputational losses for companies. This study aims to identify and analyze effective International Human Resource Management (IHRM) strategies for improving expatriate retention through a Systematic Literature Review (SLR) approach. This research utilized literature from various prominent databases, such as Scopus and Web of Science, with inclusion criteria including relevance, quality, and publication year. The analysis revealed that strategies such as pre-assignment training, cultural support, family management, competitive compensation, and guidance during and after assignments significantly contribute to expatriate retention. Additionally, the findings highlight the importance of personalized approaches in expatriate management to enhance job satisfaction and cultural adaptation. This study provides practical insights for IHRM practitioners to design programs supporting expatriate success while paving the way for future research on the influence of technology in expatriate management